A proposed radicality evaluation method for design ideas at conceptual design stage. (June 2019) - Liu, Wei; Tan, Runhua; Cao, Guozhong; Zhang, Zhengyan; Huang, Siyuan; Liu, Limeng
Highlights: A proposed radicality evaluation method assesses design ideas at conceptual stage. Technological changes value metrics used by the method come from TRIZ and BOS. The correlation between radicality and technological changes are verified. Computing algorithms are regressed on statistical analysis of known design cases. Feasibility of the method is verified by several cases regarding idea evaluation. Abstract: With the advance of technology, radical innovation plays an increasing essential role in gaining competitive advantages by leveraging the brandy new technologies such as internet of things (IoT) in product or services innovations. Although its importance is widely recognized, the mechanism of radical innovation is still poorly understood due to high level of uncertainty about its prospects. This paper aims to evaluate the radicality of design ideas from their technological changes that are the obvious and measurable characteristics of radical innovation at very beginning of their developments. To do so, a radicality evaluation method is formulated after a systematic review of studies on radical innovation and integrating of ideas evaluations methods in relevant domains. Afterwards, two radicality computing formulas are regressed through a statistical analysis of known design cases. The feasibility of the formulas is verified by a serial of recognized radical innovations followed by a case study that is related to additive manufacturing. Its application in new product development is demonstrated by a design project of adhering devices. The proposed method has potential to fertilize studies on radical innovation and knowledge-based innovation.